The analysis of obedience in Tafsir Al-Huda and its relevance in education - Ramadhan, Sulchan Ainur; Azizah, Alfiyatul; Kalong, Tasnem (Universitas Ahmad Dahlan, 2024)
Obedience is a common thing in the educational process, with obedience to educators, students can receive and learn the knowledge given. Conversely, disobedience has an impact on learning difficulties. However, the form of obedience is not widely understood in the world of education, so wrong obedience is happen in educational institutions. This study aims to analyze obedience in Tafsir Al-Huda by Bakri Syahid and its relevance in the world of education. This research was conducted with a qualitative research approach with a type of literature research. Data is collected by document techniques through primary and secondary references, then the data is analyzed by content analysis. The results of the study show that obedience can be used as a basis for learning. The forms of obedience in Tafsir Al-Huda have various meanings, namely by carrying out ordinary commands, conciousness, loyalty, consistency, and sincerity. With obedience as intended, there is relevance in education, namely character building, religion-based character education, and progressive learning. The character of obedience is very relevant in practice in the lives of students in school, family, and the environment.